The tiny guide to OpenOffice.org - Horst, Benjamin (Hentzenwerke Pub., 2004)
Annotation Home and educational computer users and company IT groups that are considering widespread deployment of OpenOffice.org will use this succinct reference to make more efficient use of the suite. The three major platforms are covered in detail: Windows, Linux, and Mac OS X making this the essential starter's guide to acquiring and using the suite. Each component--Writer, Calc, Impress, Draw, Data Source tools, Web, and the Formula tool--is treated to a thorough yet concise collection of how-to topics providing everything needed to become proficient OpenOffice users.